Strategic marketing : planning and control - Drummond, Graeme (Butterworth-Heinemann, 2001)
-- Easy to read - new user-friendly layout-- Tightly written to accommodate the reading time pressures on students-- Includes up-to-date case studiesApplicable for industry practitioners, this book cuts through the complexity and jargon surrounding planning and control subjects, providing readers with a clear, concise guide to the tools, techniques and knowledge necessary to facilitate strategic marketing decisions (analysis, formulation and implementation).The text also covers contemporary issues by exploring current developments in marketing theory and practice, including the concept of a market-led orientation and a resource/asset-based approach to internal analysis and planning.This second edition of 'Strategic Marketing: planning and control' provides a synthesis of key strategic marketing concepts, including 2 new chapters on 'competitive intelligence', as well as new vignettes and material on branding. A comprehensive text, this book is highly exam focused with all material presented having been class tested and refined.